Alokasi Waktur Kerja Keluarga dan Distribusi Pengrajin Emping Melinjo di Kabupaten Batang - Dani Isworo (STIE Widya Manggala, 2008)
Chips emping of Melinjo represent representing is wrong of especial result of agriculture commodity in Bar sub-province specially district of famous Limpung by the name of “Town Chips Emping” mostly its resident become worker of chips emping of melinjo. Finding in this research is bigger woman labour effusing allocation than men labour effusing, and found also that amount of chips emping production, amount of other opreting income and worker represent factors research also show that there are difference of earning of family without effort chips emping of melinjo with earnings of family without effort chips emping of melinjo. But difference is effort worker of chips emping of melinjo not yet can overcome distribution Iameness earnings of resident in district of Limpung.